REACTION ORDER DETERMINATION IN THIOCYANATE SPECTROPHOTOMETRIC MEASUREMENT THROUGH EXTRACTION BY FORMATION OF ION PAIR WITH THIONINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
In the article in order to study spectrophotometric measurement of thiocyanate through extraction by formation of ion pair with thionine, the partial and total order of reactions to the reactors were studied.
Keywords: thionine, thiocyanate, spectrophotometry